2017
DOI: 10.1016/j.ccell.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

ACK1/TNK2 Regulates Histone H4 Tyr88-phosphorylation and AR Gene Expression in Castration-Resistant Prostate Cancer

Abstract: SUMMARY Androgen receptor (AR) is critical for the progression of prostate cancer to castration resistant (CRPC) state. AR antagonists are ineffective due to their inability to repress the expression of AR or its splice variant, AR-V7. Here, we report that the tyrosine kinase ACK1 (TNK2) phosphorylates histone H4 at tyrosine 88 upstream of the AR transcription start site. WDR5/MLL2 complex reads the H4-Y88-phosphorylation marks and deposits the transcriptionally activating H3K4-trimethyl marks promoting AR tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(128 citation statements)
references
References 41 publications
3
119
0
Order By: Relevance
“…Recently, we have reported a new class of robust and soluble TNK2–specific small molecule inhibitor, ( R )- 9b MS [24, 25]. To address the role of TNK2 in AKT Tyr176-phosphorylation in TNBCs, cells were treated with ( R )- 9b MS. A significant decrease in TNK2 activation, as seen by loss of TNK2 Tyr-phosphorylation is observed upon ( R )- 9b MS treatment (Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have reported a new class of robust and soluble TNK2–specific small molecule inhibitor, ( R )- 9b MS [24, 25]. To address the role of TNK2 in AKT Tyr176-phosphorylation in TNBCs, cells were treated with ( R )- 9b MS. A significant decrease in TNK2 activation, as seen by loss of TNK2 Tyr-phosphorylation is observed upon ( R )- 9b MS treatment (Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…34 A recent study further reported a novel chromatinregulated mechanism of AR transcriptional regulation being mediated by the tyrosine kinase ACK1 (also known as TNK2). 35 ACK1/TNK2 phosphorylates histone H4 at Try88 upstream of the AR transcription start site, leading to WDR5/MLL2 complex-mediated increase of AR transcription, and the epigenetic regulatory circuits drive CRPC progression. Reversal of the pTry88-histone H4 epigenetic marks by the ACK1 inhibitor (R)-9bMS sensitizes naive and ADT-resistant prostate cancer cells and reduces AR expression and halts CRPC growth.…”
Section: Histone Modificationsmentioning
confidence: 99%
“…Reversal of the pTry88-histone H4 epigenetic marks by the ACK1 inhibitor (R)-9bMS sensitizes naive and ADT-resistant prostate cancer cells and reduces AR expression and halts CRPC growth. 35 LSD1 (also known as KDM1A), a FAD-dependent demethylase, functions as a transcriptional repressor of ARregulated enhancers through H3K4 and H3K9 demethylation and as an AR coactivator through interaction with RCOR1/CoREST and phosphorylation of histone H3 Thr-6 (H3T6ph). 36 LSD1 was found to promote CRPC also through epigenetic programming to induce CENPE, a centromere-binding protein and mitotic kinesin, expression.…”
Section: Histone Modificationsmentioning
confidence: 99%
“…However, since resistance to ADT has been integrally associated with epigenetic modifications and aberrant tyrosine kinase signaling, development of suitable epigenetic inhibitors likely holds promise for the future in this context. Recent reports have demonstrated the contribution of the non-receptor tyrosine kinase ACK1 in the epigenetic activation of the AR gene locus [4345]. Targeting ACK1 using an epigenetic inhibitor not only reduced full-length AR levels, but also reduced AR-V7 levels to overcome stemness-associated enzalutamide-resistance, and curb castration-resistant prostate tumor growth [43, 44].…”
Section: Role Of Tumor Plasticity In Neuroendocrine Trans-differentiamentioning
confidence: 99%